High magnetic aspects of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline NiZn ferrite, Ni0.5Zn0.5Fe2O4, having particle size in the range 6-10 mn, has been synthesized by an auto-combustion method. The nanosized ferrite powder formed at a low temperature is annealed at different temperatures in the range 473-1273 K and characterized by X-ray diffraction, vibrating sample magnetometry, Mossbauer spectroscopy, transmission electron microscopy and scanning electron microscopy. Magnetic transition temperature broadening up to 773 K is observed for the nanosized sample, compared to the T-c = 563 K for the bulk material. Critical particle diameter (D-c) is found to be similar to 40 nm at which maximum coercivity is obtained for the powder sample annealed at 973 K. Similarly, high room temperature magnetization, comparable to that of the bulk material, is obtained for the powders annealed at 1073 K, with a maximum particle size of similar to 50 nm. Very little grain growth is observed for the powders annealed above 1073 K. The results show that, optimum magnetic properties can be achieved for fine particle NiZn ferrite powders synthesized by a low-temperature auto-combustion method and processed at relatively lower temperatures.

Highly active nanostructured Co3O4 catalyst with tunable selectivity for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Vijayanand, Subramanian; Potdar, Hari S.; Joy, Pattayil Alias; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chemistry Letters, 2008)
This is a first report of highly efficient heterogeneous nanostructured Co3O4 catalyst (6-8 nm) having high surface area (95 m(2)/g) developed for selective liquid phase air oxidation of p-cresol under atmospheric pressure conditions.

High room temperature ferromagnetic moment of Ho substituted nanocrystalline BiFeO3 - Thakuria, Pankaj; Joy, Pattayil Alias (Applied Physics Letters, 2010)
Magnetic properties of trivalent rare-earth ion substituted nanocrystalline BiFeO3 have been studied for the compositions Bi0.875R0.125FeO3 (R=La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb). All compositions show ferromagnetic characteristics at room temperature, with enhanced magnetization after substitution. Very high magnetization (at 6 T), almost three times that of the unsubstituted composition, is observed for R=Ho, and highest remnant magnetization is obtained for R=Nd and Sm. The magnetic transition temperature is increased by similar to 20 K for R=La. The results show that it is possible to tune the magnetic characteristics of the nanocrystalline multiferroic BiFeO3 by the choice of the rare-earth ion. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3502481]

Highly sensitive and fast responding CO sensor based on Co3O4 nanorods - Patil, Dewyani; Patil, Pradip; Subramanian, Vijayanand; Joy, Pattayil Alias; Potdar, Hari S. (Talanta, 2010)
Co3O4 nanorods (diameters similar to 6-8 nm and lengths similar to 20-30 nm) were synthesized for the first time through a simple co-precipitation/digestion method by calcination of cobalt hydroxyl carbonate in air and their CO gas sensing properties were investigated. The Co3O4 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 6.55-50 ppm CO gas at 250 degrees C), extremely rapid response (similar to 3-4s), fast recovery (similar to 5-6s), excellent repeatability, good selectivity and lower operating temperature (similar to 250 degrees C). Furthermore, the Co3O4 nanorods are able to detect up to 5 ppm for CO with reasonable sensitivity (similar to 3.32) at an operating temperature 250 degrees C and they can be reliably used to monitor the concentration of CO over the range (5-50 ppm). The experimental results clearly demonstrate the potential of using the Co3O4 nanorods as sensing material in the fabrication of CO sensors. Plausible CO sensing mechanism of the Co3O4 nanorods is also discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CO sensor; Co3O4 nanorods; HRTEM; Semiconductor gas sensors; XPS; XRD

High magnetostriction and coupling coefficient for sintered cobalt ferrite derived from superparamagnetic nanoparticles - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Applied Physics Letters, 2012)
High magnetostriction (lambda) and coupling coefficient (d lambda/dH) of 315 ppm and 1.97 x 10(-9) A(-1) m, respectively, are obtained at room temperature for sintered cobalt ferrite derived from nanocrystalline powders. Also, the powder was compacted at a low pressure of 8 MPa and sintered for a short duration of 10 min at 1450 degrees C. Magnetic annealing at 300 degrees C in a field of 0.5 T for 30 min further enhanced the magnetostriction coefficient to 345 ppm with a higher coupling coefficient 2.12 x 10(-9) A(-1)m. The magnetic field above which maximum magnetostriction is observed is reduced by almost half after magnetic annealing. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4745922]

High magnetostriction coefficient of Mn substituted cobalt ferrite sintered from nanocrystalline powders and after magnetic field annealing - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Current Applied Physics, 2013)
Magnetostriction characteristics of Mn substituted cobalt ferrite, CoFe2-xMnxO4 (0 <= x <= 0.3), sintered from nanocrystalline powders of average particle size of similar to 4 nm have been studied. Larger value of magnetostriction at lower magnetic field is achieved after substitution of Mn for Fe. The maximum value of magnetostriction coefficient is not much affected and the slope of the magnetostriction is increased with increasing Mn content. Higher maximum value of magnetostriction coefficient (lambda) of 234 ppm comparable to that of the unsubstituted composition with larger strain derivative (d lambda/dH) is obtained for x = 0.2 in CoFe2-xMnxO4. The magnetostriction coefficient is increased to 262 ppm with further enhancement in the strain derivative after annealing the sintered compact at 300 degrees C in a magnetic field of 400 kA/m for 30 min. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetic field annealing; Magnetostriction; Mn substitution; Nanocrystalline

High magnetostriction parameters for low-temperature sintered cobalt ferrite obtained by two-stage sintering - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of Magnetism and Magnetic Materials, 2014)
From the studies on the magnetostriction characteristics of two-stage sintered polycrystalline CoFe2O4 made from nanocrystalline powders, it is found that two-stage sintering at low temperatures is very effective for enhancing the density and for attaining higher magnetostriction coefficient. Magnetostriction coefficient and strain derivative are further enhanced by magnetic field annealing and relatively larger enhancement in the magnetostriction parameters is obtained for the samples sintered at lower temperatures, after magnetic annealing, despite the fact that samples sintered at higher temperatures show larger magnetostriction coefficients before annealing. A high magnetostriction coefficient of similar to 380 ppm is obtained after field annealing for the sample sintered at 1100 degrees C, below a magnetic field of 400 kA/m, which is the highest value so far reported at low magnetic fields for sintered polycrystalline cobalt ferrite. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetostriction; Two-stage sintering